2022
DOI: 10.1002/adfm.202201205
|View full text |Cite
|
Sign up to set email alerts
|

In‐situ Polymerized Gel Polymer Electrolytes with High Room‐Temperature Ionic Conductivity and Regulated Na+ Solvation Structure for Sodium Metal Batteries

Abstract: Sodium metal batteries (SMBs) are promising candidates for low‐cost but high‐energy energy storage applications. Both long‐term stability and safety of SMBs can be largely enhanced when liquid electrolytes (LEs) are replaced by gel polymer electrolytes (GPEs). However, the low room‐temperature (RT) ionic conductivity and inferior interfacial compatibility of GPEs severely restrain their practical use. Herein, a poly(butyl acrylate)‐based GPE with a high RT ionic conductivity of 1.6 mS cm−1 is developed by in‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…The PVH membrane was treated with a basic KOH solution to generate C�C and C�O groups by dehydrofluorination (see FT-IR and XPS spectra in Figures S3 and S4), 25,26 where the unsaturated C�C moieties act as anchoring sites of PEG methyl ether thiol by the photoinitiated thiol-ene click reaction. The resulting PVH−PEG membrane contains 1.1 mol % of PEG, which was quantitatively determined by 1 H and 19 F NMR spectroscopy methods (Figure S5). It was found that the porous PVH structure is preserved well after the postmodification as shown in the SEM image of PVH−PEG in Figure S6, demonstrating that PEG grafting has not altered the membrane structure including pore size and morphologies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The PVH membrane was treated with a basic KOH solution to generate C�C and C�O groups by dehydrofluorination (see FT-IR and XPS spectra in Figures S3 and S4), 25,26 where the unsaturated C�C moieties act as anchoring sites of PEG methyl ether thiol by the photoinitiated thiol-ene click reaction. The resulting PVH−PEG membrane contains 1.1 mol % of PEG, which was quantitatively determined by 1 H and 19 F NMR spectroscopy methods (Figure S5). It was found that the porous PVH structure is preserved well after the postmodification as shown in the SEM image of PVH−PEG in Figure S6, demonstrating that PEG grafting has not altered the membrane structure including pore size and morphologies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Optical photographs; FT-IR spectra; XPS spectra; 1 H and 19 F NMR spectra; ionic conductivities and electrolyte uptakes; SEM images and EDS mapping results; galvanostatic cycling profiles; and EIS spectra (PDF)…”
Section: ■ Associated Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the design and fabrication of advanced gel electrolytes are of the utmost importance for the realization of safe SMBs with excellent performance [117,118] . Wen et al designed a new photopolymerized gel electrolyte of ETPTA-NaClO 4 -QSSE, which exhibited unprecedented room-temperature ionic conductivity of 1.2 mS cm -1 , a wide electrochemical window up to 4.7 V (vs. Na + /Na), and outstanding compatibility with Na metal anode [119] . Due to its enhanced interfacial stability, Na symmetric cells based on this electrolyte showed superior long-term cycling performance and morphology of dendrite-inhibited SMAs.…”
Section: Polymer Electrolytesmentioning
confidence: 99%